Syndrome in question - Catharina Maria Freire de Lucena Pousa; Fernanda Guedes Lavorato; Fernanda Valente Rehfeldt; Danielle Mann; Maria de Fátima Gonçalves Scotelaro Alves (Sociedade Brasileira de Dermatologia, 2015)
AbstractMuir-Torre syndrome is a rare genodermatosis characterized by the occurrence of at least one sebaceous tumor associated with visceral neoplasia, but with no predisposing factors. The sebaceous neoplasm may appear before, during or after the diagnosis of colorectal cancer. As it is regarded as a subtype of nonpolyposis hereditary colorectal cancer, it is important to evaluate the patient's first-degree relatives. The clinical course of the neoplasm is usually more indolent and the syndrome has a good prognosis. We report the case of a patient who, after a ten-year diagnosis of colorectal cancer, presented with multiple sebaceous neoplasms.